Analisis Banjir Metode Hidrograf Satuan Sintetis SCS dan Nakayasu DAS Pesung, Batam - Ayuni, Tiara Puspita; Saputra, Ade Jaya; Ginting, Jody Martin (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2023)
Design discharge is discharge with a certain return period which is used as a reference or parameter in a water building construction planning. Calculation of the design discharge can be done by using the synthetic unit hydrograph method. The calculation of the planned discharge using the Nakayasu and SCS-CN synthetic unit hydrographs aims to compare the calculation of the maximum discharge in the Pesung Watershed, Batam. The design discharge analysis was carried out without calibrating with AWLR data (observed flow) due to the unavailability of AWLR data at the study site. Thus, in this study using HDRO (high direct runoff) as a comparison. The purpose of this study is to estimate the magnitude of the design flood discharge in the Pesung Watershed, Batam City. The methods used in this calculation of the flood hydrograph is using an empirical formula, namely SCS Synthetic Unit Hydrograph and Nakayasu. The results of the HDRO calculation analysis show that the largest flood discharge occurs in the Nakayasu synthetic unit hydrograph method with details of the SCS synthetic unit hydrograph method, the peak time (Tp) is obtained at 4.46 hours, with a return period flood discharge of 5 – 50 reaching 215,488 – 584,308 m3/ s. Whereas in the Nakayasu synthetic unit hydrograph method, the peak time (Tp) is obtained at 1.47 hours, with a return period flood discharge of 5 – 50 years reaching 360.526 – 986.535 m³/s.